Improving Reading Comprehension by Using Fable Text of the Nineth Grade Students of SMP Negeri 1 Palu - Ian Putri Pertama; Wahyudin Wahyudin; Maf’ulah Maf’ulah; Sriati Usman (Journal of General Education and Humanities, 2026)
This research aims to determine the effectiveness of using fable texts in improving the reading comprehension skills of ninth-grade students of SMP Negeri 1 Palu. Reading comprehension is an essential skill in English learning; however, many junior high school students still struggle to understand texts due to limited vocabulary and low reading interest. Therefore, engaging narrative texts, such as fables, are considered a potential alternative to address this issue. This type of research is quasi-experimental, with a pre-test and post-test control-group design. The population in this study comprised all ninth-grade students at SMP Negeri 1 Palu in the 2024/2025 academic year, totaling 352 students and divided into 11 classes. The sampling technique used was cluster random sampling, so two classes were selected as the research sample, with one class serving as the experimental group and the other as the control group. The experimental group was taught using fable texts, while the control group was taught using conventional learning methods. Research data were obtained through reading comprehension tests administered before the treatment (pre-test) and after the treatment (post-test). The collected data were analyzed using descriptive statistics and inferential statistical tests to determine the significance of the treatment effect. The results showed a significant increase in students' reading comprehension skills when taught using fable texts compared to those taught using conventional methods. The average post-test score of the experimental group reached 93.55, while the control group obtained 88.39, with a significance value of 0.007 (sig. < 0.05). These findings indicate that the difference between the two groups was statistically significant. This shows that the use of fable texts has a positive, significant effect on students' reading comprehension.